2022
DOI: 10.1038/s41598-022-09184-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of severe acute malnutrition among children aged 6–36 months in Kalafo district (riverine context) of Ethiopia

Abstract: Malnutrition remains prevalent and existing health problem globally. Particularly Undernutrition is a major public health issue in developing countries. Globally the causes of severe acute undernutrition varies across context. The aim of this study was to identify the determinants of severe acute malnutrition to uncover contextual factors based on UNICEF conceptual framework, as there was no study done in a similar context in Ethiopia. Health facility based (health post) un-matched case control study with Key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(67 reference statements)
6
2
0
Order By: Relevance
“…These results are close to those of similar studies conducted in Nepal [17], in certain rural areas of India [18], and in Ethiopia [19,20]. These results corroborate those of a study conducted by Ahmed AT et al in the Kalafo district of Ethiopia [21] which indicated that risks of suffering from SAM were higher among children from households with at least three children under the age of ve than among children from households with fewer than three children under the age of ve. This could be explained by the fact that increasing household size increases the burden of distributing resources, including food, to feed each member of the household especially young children.…”
Section: Discussionsupporting
confidence: 92%
“…These results are close to those of similar studies conducted in Nepal [17], in certain rural areas of India [18], and in Ethiopia [19,20]. These results corroborate those of a study conducted by Ahmed AT et al in the Kalafo district of Ethiopia [21] which indicated that risks of suffering from SAM were higher among children from households with at least three children under the age of ve than among children from households with fewer than three children under the age of ve. This could be explained by the fact that increasing household size increases the burden of distributing resources, including food, to feed each member of the household especially young children.…”
Section: Discussionsupporting
confidence: 92%
“…In line with other studies conducted in different parts of Ethiopia, this study found that diarrheal disease in the last two weak before the interview was found to be positively associated with being underweight (13,16,26,33). This may be because, infectious diseases play a major role in undernutrition as they result in increased needs and high energy expenditure, lower appetite, nutrient losses due to vomiting, poor digestion, mal-absorption, and the utilization of nutrients and disruption of metabolic equilibrium (34).…”
Section: Discussionsupporting
confidence: 91%
“…Children with age falling within the range of 6 to 11 months were predominant (22; 36.6%), followed by those falling within the range of 12 to 23 months (20; 33.3%). This was in line with studies done in Ethiopia [17,18], Niger [19], and Ghana [20].…”
Section: Sociodemographic Characteristics Of Children and Their Motherssupporting
confidence: 92%